Spatiotemporal expansion of dengue in Brazilian Amazon between 2001 and 2021 - Ravena dos Santos Hage; Bianca Conrad Bohm; Caio Perez Casagrande; Suellen Caroline M. Silva; Alessandra Talaska Soares; Jackeline Vieira Lima; Nádia Campos Pereira Bruhn; Fábio Raphael Pascoti Bruhn (Scientific Reports)
Abstract Dengue remains a significant public health concern in Brazil, with all federative units registering occurrences of the disease within their territories despite constant measures to control the Aedes aegypti vector. This study aimed to evaluate the profile of notified dengue cases in the Brazilian Legal Amazon from 2001 to 2021, analyzing National System of Notifiable Diseases (SINAN) data on the disease to assess the risks for its occurrence. Subsequently, statistical analyses were conducted to identify incidence and lethality rates. Over the study period, approximately 1,344,950 cases of the disease were reported, resulting in 863 deaths. The transmission of cases in the Amazonian states was not homogeneous, demonstrating variations and clusters over the years of extreme value for health authorities. Identifying and understanding the spatiotemporal patterns for the disease in the region helps assess the behavior of infections in areas with high susceptibility, promoting targeted interventions and resource allocation for dengue control programs. It is important to encourage future studies that evaluate the disease’s risk based on quantitative variables. Such studies contribute to the formulation of health policies aimed at controlling and preventing dengue, improving public health outcomes.